Peran Pajak sebagai Instrumen Kebijakan Fiskal dalam Mengantisipasi Krisis Ekonomi pada Masa Pandemi Covid-19 - Fauziah Aqmarina; Imahda Khoiri Furqon (Fakultas Ekonomi Dan Bisnis Islam IAIN Metro, 2020)
Abstract Tax is one of the fiscal policy instruments that affect the economic development of a country. The purpose of research is to analyze the role of taxes as a fiscal policy instrument in anticipating the economis crisis during the pandemic covid-19. This research method uses a qualitative research method with a descriptive type of approuch used to describe in depth the role of taxes as a fiscal policy instrument in national taxation praxis during the covid-19 period. The result of this research show that taxes play a role as a fiscal policy instrument with a combination of regular functions and economic stabilization to maintain conditions of contraction and relaxation of the national economy which has flexibility for sustainable state revenues; distribution for public welfare while maintaining the stabilization of economic growth that supports national development is one of the determining factors for the success of fiscal policy in increasing investment competitiveness and anticipating a weakening of the global economy. Keywords: Tax, Fiscal Policy, Economy Crysis, Covid-19